2013
DOI: 10.1016/j.micpath.2012.11.010
|View full text |Cite
|
Sign up to set email alerts
|

Dendritic cells and vaccine design for sexually-transmitted diseases

Abstract: Dendritic cells (DCs) are major antigen presenting cells (APCs) that can initiate and control host immune responses toward either immunity or tolerance. These features of DCs, as immune orchestrators, are well characterized by their tissue localizations as well as by their subset-dependent functional specialties and plasticity. Thus, the level of protective immunity to invading microbial pathogens can be dependent on the subsets of DCs taking up microbial antigens and their functional plasticity in response to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 187 publications
(159 reference statements)
1
12
0
Order By: Relevance
“…LOX-1 was also expressed at low levels on vCD14 - DCs (Figure 7 b,c). Transcriptional levels of CD207 were low in all vaginal APC subsets, despite detectable protein levels on the surface of vLCs (Figure 1 b), as previously reported [ 5 , 6 ]. DC-ASGPR was detected in a few vLCs and approximately 50% (49.06 ± 25) of vCD14 - DCs (Figure 7 b, c).…”
Section: Resultssupporting
confidence: 85%
See 3 more Smart Citations
“…LOX-1 was also expressed at low levels on vCD14 - DCs (Figure 7 b,c). Transcriptional levels of CD207 were low in all vaginal APC subsets, despite detectable protein levels on the surface of vLCs (Figure 1 b), as previously reported [ 5 , 6 ]. DC-ASGPR was detected in a few vLCs and approximately 50% (49.06 ± 25) of vCD14 - DCs (Figure 7 b, c).…”
Section: Resultssupporting
confidence: 85%
“…Finally, it is important to note that the individual APC populations we describe in this manuscript may contain additional levels of heterogeneity. For example, we have previously shown that both CD14 - and CD14 + LP-DCs could be further separated into two subpopulations based on CD1a expression [ 5 , 6 ]. Further studies, such as single-cell RNA sequencing of populations of interest, are warranted to further characterize the heterogeneity of these populations.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Identification of miRNAs encoded by DNA viruses indicate that viruses have evolved to build on RNA silencing to regulate host and viral genes. miRNAs encoded by viruses can affect the viral life cycle and host physiology . Herpes simplex virus (HSV)‐1 and HSV‐2 are two members of a group of pathogenic human viruses belonging to the alphaherpesvirus subfamily .…”
Section: Introductionmentioning
confidence: 99%